The Effects of Hot Water Treatments on Survival of Heterodera schachtii - Steele, A E (Journal of nematology, 1973)
Cysts of Heterodera schachtii were treated in a water bath at constant temperatures ranging from 45 - 62.5 C for 1 sec to 28 hr. Treated and untreated cysts were incubated 8 weeks in sugarbeet root diffusate at 24 C to measure emergence of surviving larvae. Within the temperature range of 49 - 54 C, the minimum lethal temperature was proportional to the log time of treatment. No larvae emerged from cysts exposed 10 sec at 60 C. Although treatment of cysts for 8 hr at 45 C significantly reduced emergence, increasing the treatment period to 28 hr did not completely suppress emergence